Waste Water Treatment Technologies and Recent Analytical Developments - Sebastian García Einschlag, Fernando; Carlos, Luciano (IntechOpen, 2013)
The generation of wastes as a result of human activities has been continuously speeding up since the beginning of the industrial revolution. Hence, both optimized waste water treatment technologies and modern tools to assess the effects of pollution sources are necessary to prevent the contamination of aquatic ecosystems The book offers an interdisciplinary collection of topics concerning waste water treatment technologies, water quality monitoring and evaluation of waste water impact on natural environments. We hope that this publication will be helpful for graduate students, environmental professionals and researchers of various disciplines related to waste water.